Recent Developments on N-Heterocyclic Carbene Supported Zinc Complexes: Synthesis and Use in Catalysis - Dagorne, Samuel (Synthesis, 2018)
The present contribution reviews the synthesis, reactivity, and use in catalysis of NHC–Zn complexes reported since 2013. NHC-stabilized Zn(II) species typically display enhanced stability relative to common organozinc species (such as Zn dialkyls), a feature of interest for the mediation of various chemical processes and the stabilization of reactive Zn-based species. Their use in catalysis is essentially dominated by reduction reactions of various unsaturated small molecules (including CO2), thus primarily involving Zn–H and Zn–alkyl derivatives as catalysts. Simple NHC adducts of Zn(II) dihalides also appear as effective catalysts for the reduction amination of CO2 and borylation of alkyl/aryl halides. Stable and well-defined Zn alkoxides have also been prepared and behave as effective catalysts in the polymerization of cyclic esters/carbonates for the production of well-defined biodegradable materials. Overall, the attractive features of NHC-based Zn(II) species include ready access, a reasonable stability/reactivity balance, and steric/electronic tunability (through the NHC source), which should promote their further development.1 Introduction2 NHC-Supported Zinc Alkyl/Aryl Species2.1 Synthesis2.2 Reactivity and Use in Catalysis3 NHC-Supported Zinc Hydride Species3.1 Synthesis3.2 Reactivity and Use in Catalysis4 NHC-Supported Zinc Amido/Alkoxide Species4.1 Synthesis4.2 Use in Catalysis5 NHC-Supported Zinc Dihalide Species5.1 Synthesis5.2 Use in Catalysis6 Other NHC-Stabilized Zn Species7 Conclusion
Keywords: N-heterocyclic carbenes; zinc; catalysis; hydrosilylation; carbon dioxide; reduction; polymerization